Reseña/Review (Bauman, Z., Lyon, D., Liquid surveillance. Cambridge: Polity Press, ISBN: 978-0-745-66282-4, 152 págs., 2013) - Tolan, Claire (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2015)
Reseña/Review (Bauman, Z., Lyon, D., Liquid surveillance. Cambridge: Polity Press, ISBN: 978-0-745-66282-4, 152 págs., 2013)